The Influence Of Organizational Culture And Work Environment On Employee Performance Through Work Motivation As An Intervening Variable At The Department Of Food Security, Agriculture, And Fisheries In Banten Province - Yeni Marliana; Uli Wildan Nuryanto; Khaeruman Khaeruman (Amkop Management Accounting Review (AMAR), 2026)
This study aims to analyze the influence of organizational culture and work environment conditions on employee performance, with work motivation as a mediating variable, at the Food Security, Agriculture, and Fisheries Service in Banten Province. Employee performance is seen as an indicator of individual achievement in carrying out tasks according to their roles and responsibilities within the organization. The approach used is a quantitative method with a population of all employees at the Food Security, Agriculture, and Fisheries Service of Serang City, the Agriculture and Food Security Service of Pandeglang Regency, and the Fisheries Service of Serang Regency, totaling 386 people. Of the total population, 230 employees were designated as research samples. Primary data were obtained through questionnaires distributed via Google Forms, and the analysis employed statistical methods within a quantitative framework using Partial Least Squares (PLS). The research findings revealed that organizational culture significantly influences employee performance, while the work environment showed no significant direct effect. However, both variables were shown to significantly influence work motivation. Furthermore, organizational culture and the work environment also exert an indirect influence on performance through work motivation. Therefore, work motivation acts as an intervening variable that strengthens the relationship between organizational culture and the work environment and employee performance at the Banten Province Food Security, Agriculture, and Fisheries Service.